2008
DOI: 10.1038/sj.bjp.0707526
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response and cardioprotection during open‐heart surgery: the importance of anaesthetics

Abstract: Open-heart surgery triggers an inflammatory response that is largely the result of surgical trauma, cardiopulmonary bypass, and organ reperfusion injury (e.g. heart). The heart sustains injury triggered by ischaemia and reperfusion and also as a result of the effects of systemic inflammatory mediators. In addition, the heart itself is a source of inflammatory mediators and reactive oxygen species that are likely to contribute to the impairment of cardiac pump function. Formulating strategies to protect the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
1
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 213 publications
(243 reference statements)
2
108
1
16
Order By: Relevance
“…[8][9][10] This study demonstrated this condition; the secretion of IL-6 (a proinflammatory cytokine) increased markedly at the anhepatic stage, while the secretion of IL-10 (an antiinflammatory cytokine) was prominent at the neohepatic stage. Interleukin-6 is a cytokine actively secreted during major surgeries (eg, cardiopulmonary bypass), [11][12][13][14] and its concentration is closely related with postoperative prognosis. 15,16 Interleukin-10, which is secreted by activated helper T lymphocytes and induced by TNF-α secreted from monocytes, 17,18 suppresses the release of proinflammatory cytokines such as TNF-α, IL-1β, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] This study demonstrated this condition; the secretion of IL-6 (a proinflammatory cytokine) increased markedly at the anhepatic stage, while the secretion of IL-10 (an antiinflammatory cytokine) was prominent at the neohepatic stage. Interleukin-6 is a cytokine actively secreted during major surgeries (eg, cardiopulmonary bypass), [11][12][13][14] and its concentration is closely related with postoperative prognosis. 15,16 Interleukin-10, which is secreted by activated helper T lymphocytes and induced by TNF-α secreted from monocytes, 17,18 suppresses the release of proinflammatory cytokines such as TNF-α, IL-1β, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon-like peptide-1, an incretin hormone, was found to reduce circulating IL-6 levels in humans (48). Ischemic conditioning (pre and post) is a potential protective measure for prolonged ischemia and associated cytokine release (43). Plasma filtration was successful in cytokine removal but was associated with albumin loss.…”
Section: Il-6 Removalmentioning
confidence: 99%
“…The risk factors triggering IL-6 activities may include increasing age (in particular older age >70 years), obesity, atherosclerosis, diabetes (42), hepatic and renal dysfunction, high postoperative oxygen consumption and adrenaline infusions (43), etc.…”
Section: Risk Factors Of Il-6 Activitionmentioning
confidence: 99%
“…Several membrane receptors seems to be involved in the phenomenon of ischemic preconditioning including -1, , opioid and adenosine receptors (19). In cardiac surgery, the observed systemic inflammatory response is the result of direct surgical trauma, ischemia-reperfusion injury and extracorporeal circulation (20) and cardiac injury can be triggered by ischemia, reperfusion, and also by local effects of mediators of the inflammatory response. Additionally, the heart itself may release locally inflammatory mediators and oxygen free radicals that can contribute to the worsening of the cardiac function.…”
Section: Myocardial Protectionmentioning
confidence: 99%